Beyond philanthropy: Modelling zakat’s systemic role in circular economic practices and sustainable finance - Muhammad Putra Aprullah; Muhammad Sayuthi; Salsabilla Julnadi; William Ben Gunawan; Indrayani Indrayani (Privietlab, 2026)
This study systematically examines the role of zakat in promoting sustainable finance and achieving Sustainable Development Goals (SDGs). Through the Systematic Literature Review (SLR) method, this study identifies, analyzes, and synthesizes various empirical studies and national data related to zakat’s contribution to economic, social, and environmental development. Zakat, as an Islamic social finance instrument, has great potential in strengthening the inclusive financial ecosystem and supporting community welfare. The literature review shows that zakat plays a significant role not only as a financial instrument for redistributing prosperity but also as a catalyst for sustainable development through environmental conservation, economic empowerment, enhanced social resilience, and increased financial inclusion. The integration of zakat into the sustainable finance policy framework has been proven to support the achievement of several SDGs, particularly the goals of poverty eradication (SDG 1), decent work and economic growth (SDG 8), and inequality reduction (SDG 10). Therefore, zakat’s potential can be optimized through good governance, digital innovation, and cross-sector collaboration is a strategic key to accelerate the realization of sustainable finance and achieve the SDGs in Indonesia